Paradoxes in Design Thinking. (28th July 2017) - Rodgers, Paul A.; Innella, Giovanni; Bremner, Craig
Abstract: This paper presents a critical examination of the current state of design by exploring a number of paradoxes – sustaining the unsustainable, disciplining the undisciplined, reconciling future visions with harsh realities, and others. We suggest that whilst design researchers have been probing design, it is highly likely design might never have been where they were looking. Consequently, this paper presents a 6 point manifesto for design research where the emphasis is on acknowledging our material and energy flows and their environmental impact, a more critical stance in design culture that will reveal contradictions, rock the boat, critique 'what is' to 'what could be', and contest the legitimisation of power. Moreover, design must strive to maintain care for details and quality of public service in everything we do whilst having a concern for otherness and visuality, which privileges thinking in terms of images over numbers and texts, and an interest in theory.